2011
DOI: 10.1017/s0007485311000447
|View full text |Cite
|
Sign up to set email alerts
|

Offspring production and self-superparasitism in the solitary ectoparasitoidSpalangia cameroni(Hymenoptera: Pteromalidae) in relation to host abundance

Abstract: Parasitoid fitness strongly depends on the availability and quality of hosts, which provide all resources required for larval development. Several factors, such as host size and previous parasitation, may affect host quality. Because self-superparasitism induces competition among a female's offspring, it should only occur if there is an imperfect recognition of self-parasitized hosts or if there is a fitness advantage to self-superparasitism. Against this background, we investigated self-superparasitism and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
1
13
1
Order By: Relevance
“…As a solitary parasitoid, only one offspring could survive to adult in a host. Self superparasitism will increase competition among siblings (Darrouzet et al ., ; Böckmann et al ., ), so it often means a waste of time and eggs for A. gifuensis females when enough healthly hosts are available; further, hosts that had already been parasitized are generally of low host quality, and in turn, cause low quality offspring. Self superparasitism rate of A. gifuensis on two hosts increased as the host density decreased.…”
Section: Discussionmentioning
confidence: 99%
“…As a solitary parasitoid, only one offspring could survive to adult in a host. Self superparasitism will increase competition among siblings (Darrouzet et al ., ; Böckmann et al ., ), so it often means a waste of time and eggs for A. gifuensis females when enough healthly hosts are available; further, hosts that had already been parasitized are generally of low host quality, and in turn, cause low quality offspring. Self superparasitism rate of A. gifuensis on two hosts increased as the host density decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data obtained in previous studies on the parasitism capacity shown by S. cameroni (Tormos et al, , , ; Boeckmann et al, ), various C. capitata pupae densities (2, 4, 6, 8, 10, 14, 20, 30 and 40) were exposed to S. cameroni mated (=fertilised) females. One S. cameroni mated female was initially used per density.…”
Section: Methodsmentioning
confidence: 99%
“…In this experiment, adults of P. rufipes and S. cameroni mated females were, again, obtained from laboratory colonies. Various C. capitata pupae densities (2, 4, 6, 8, 10, 14, 20, 30 and 40) – established according to previous studies of parasitism/predation capacity on C. capitata pupae, shown by both natural enemies (Monzó et al, , ; Tormos et al, , , ; Boeckmann et al, ) – were exposed to parasitoids and predators together. One P. rufipes adult and one S. cameroni mated female were initially used per density but the experiment was repeated with three times larger the initial numbers of the host, parasitoid and predator as explained above for previous experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parasitoid Microplitis rufiventris (Hymenoptera: Braconidae), superparasitism increases the success rate of emergence of wasp larvae when using a suboptimal host (advanced host) 8 . In the parasitoid Spalangia cameroni (Hymenoptera: Pteromalidae), when hosts are scare, superparasitism is observed and offspring production per parasitized host increases 9 . Superparasitism can help larvae of the parasitoid Pseudapanteles dignus evade host encapsulation 10 .…”
Section: Introductionmentioning
confidence: 99%